Morphological and molecular identification characterization of Neopestalotiopsis species associated with leaf spot on oil palm (Elaeis guineensis Jacq) - Norddin, Syahida (2016)
Oil palm (Elaeis guineensis) is a tropical perennial plant species in the family Arecacea that grows in Malaysia. It is an economically important crop which the oil palm cultivation area is more than 4.49 million hectares and also producing 17.73 million tonnes of palm oil and 2.13 tonnes of palm kernel oil. Leaf spot is one of the common problem in oil palm plantation, although it does not cause significant impact on oil palm production. The symptoms of these leaf spot are brown, small, oval to irrigular lesions and later, the lesions expand coalesc and form black lesions. In Malaysia, there is limited research on the composition of fungal pathogens causing leaf spot of oil palm. The objectives of this studies are 1) to isolate pure cultures of fungal isolates causing leaf spot of on oil palm; 2) to identify fungal pathogens to species level based on morphological characteristics and polymerase chain reaction (PCR) protocol using ITS 4 and ITS 5 primers; and 3) to construct internal transcribed spacer (ITS) phylogeny of the fungal species using Bayesian analysis. In these studies, symptomatic leaves were collected from five different oil palm trees at Ladang Heavea, University Putra Malaysia (UPM), Selangor. Infected tissues (5× 5mm) from the lesion margin were surface disinfected for 2 min with 10% chlorox and were transferred on potato dextrose agar (PDA). The pure fungal isolate isolated from leaf lesions were identify by in vitro morphological and cultural characteristics. The fungal isolates were sub-cultured by single spore isolation and the representative isolate is characterized further. DNA genomic were extracted from fresh fungal mycelium using the Dneasy Plant Mini Kit. The internal transcribed spacer (ITS) region of the ribosomal DNA were amplified using primer ITS4 and ITS5. The PCR product of the ITS were sequenced and analyzed using BLAST nucleotide search in GenBank. Based on the conidial morphology, the morphotypes of Pestalotiopsis were identified. From phylogenetic analysis using maximum likelihood method of combine datasets, the isolates from oil palm leaflets was corresponded to Neopestalotiopsis. Therefore, the present study showed that the isolates associated with leafspot of oil palm belong to Neopestalotiopsis. Based on the result of morphological characteristics of isolated fungi, it cannot to be distinguished between genus of Pestalotiopsis and genus of Neopestalotiopsis clearly. Studies on the taxonomy and fungal biodiversity of pathogenic leaf spots are important and a motivation for obtaining this knowledge is that it may set the stage for development of more efficient control management practices in oil palm plantation.